Konsumsi Diet Tinggi Lemak Tinggi Fruktosa dalam Jangka Panjang Menurunkan Sensitivitas Insulin dan Merusak Pulau Langerhans pada Tikus Sprague Dawley: Long-Term Consumption of High-Fat-High-Fructose Diet Decreased Insulin Sensitivity and Damaged the Islets of Langerhans on Sprague Dawley Rats - Kurniawati, Adelya Desi; Kuswandari, Luh Shanti; Hidayanti, Alfiani; Kusumastuty, Inggita; Sulistyowati, Etik; Handayani, Dian (Amerta Nutrition, 2025)
Background: Obesity is linked to the rising incidence of type 2 diabetes, with excessive dietary fat intake being one of the primary causes. The development of fat animal models has been discovered to be a standard experimental strategy based on replicating human behaviour in food consumption. Objectives: This study aims to investigate how long-term consumption of a high-fat, high-fructose (HFHF) diet affects the indicators of diabetes mellitus in Sprague Dawley (SD) rats, such as insulin sensitivity, by measuring the HOMA-IR, counting beta cells, and analyzing the histology of the pancreas. Methods: This experiment was conducted with 36 male SD rats in normal and HFHF groups. The normal groups had a modified AIN-93 M, while the HFHF group received a high-fat diet with 30% fructose-based water. Feed and beverage intakes were monitored every 24 hours to calculate daily caloric consumption (energy intake) for 17 weeks. Results: The results demonstrated a significant difference between the normal and HFHF groups in the HOMA-IR levels (insulin sensitivity) and number of pancreatic beta cells (p-value<0.05). This implied that following 17 weeks of HFHF intake, the HOMA-IR level of insulin sensitivity was reduced. However, the islet of Langerhans in pancreatic histopathology seemed damaged in the HFHF rats, as evidenced by the changes in their shape and lower beta cell number. Conclusions: Consuming the HFHF diet over an extended period increased glucose level, decreased insulin sensitivity, and damaged pancreatic histopathology.